The clinical application of metagenomic next-generation sequencing in sepsis of immunocompromised patients - Li, Xingxing; Liang, Shunda; Zhang, Dan; He, Miao; Zhang, Hong (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Background: Metagenomic next-generation sequencing (mNGS) was commonly applied given its ability to identify and type all infections without depending upon culture and to retrieve all DNA with unbiasedness. In this study, we strive to compare outcomes of mNGS with conventional culture methods in adults with sepsis, to investigate the differences between the immunocompromised and control group, and to assess the clinical effects of mNGS. Methods: In our study, 308 adult sepsis patients were included. We used both mNGS and conventional culture methods to analyze diagnostic results, pathogens, and sample types. The correlation between some laboratory testings and the frequency of pathogen by groups was also analyzed. Furthermore, the clinical impacts of mNGS were estimated. Results: 308 samples were assigned into immunocompromised group (92/308,29.9%) and control group (216/308,70.1%). There was the sensitivity of mNGS considered greater than that of culture method in all samples (88.0% vs 26.3%; P < 0.001), in immunocompromised group (91.3% vs 26.1%; P < 0.001), and in control group (86.6% vs 26.4%; P < 0.001), particularly in all sample types of blood (P < 0.001), BALF (P < 0.001), CSF (P < 0.001), sputum (P < 0.001) and ascitic fluid (P = 0.008). When examining the mNGS results between groups, Pneumocystis jirovecii (P < 0.001), Mucoraceae (P = 0.014), and Klebsiella (P = 0.045) all showed significant differences. On the whole, mNGS detected more pathogens than culture approaches (111 vs 25), found 89 organisms that were continuously overlooked in entire samples by culture approaches, and showed a favorable positive clinical effect in 76.3% (235 of 308) of patients. In 185 (60.1%) patients, mNGS prompted a modification in the course of management, which included antibiotic de-escalation in 61(19.8%) patients. Conclusions: The research discovered that mNGS was more sensitive than culture method, particularly in samples of blood, BALF, CSF, sputum, and ascitic fluid. When examining the mNGS results, Pneumocystis jirovecii and Mucoraceae were the pathogens seen more commonly in immunocompromised patients with sepsis, which required more attention from clinicians. There was a substantial benefit of mNGS in enhancing the diagnosis of sepsis and advancing patient treatment.